THE EFFECTIVENESS OF SCIENCE COMIC ON THE MATERIALS OF SOUND AND HEARING BASED ON PROBLEM BASED LEARNING TOWARD JUNIOR HIGH SCHOOL STUDENTS’ LEARNING MOTIVATION AND OUTCOME - Praptiwi, Ucca Swastika; Pamelasari, Stephani Diah; Parmin, Parmin (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
The objective of this research is to measure the effectiveness of science comics for sound and auditory system material based on problem based learning on motivation and learning outcomes of junior high school students. This research is quasi experiment with nonequivalent control group design. The sample was taken by using purposive sampling technique. The sample of this research was VIII E (experimental group) and VIII F (control group) in SMP N 10 Magelang. The writer collected the data by using test (cognitive learning outcomes), questionnaires (learning motivation) and observation (psychomotor learning outcomes). The result of the research indicated that the average of students learning motivation in experimental group in each indicator was higher than the control group. Consider to learning motivation there are significant contradiction between experimental and control group for the result in each indicator. The result of N-gain calculation showed that students cognitive learning of experimental group classified as medium category with the N-gain score of 0.39, while the control group classified as low category the N-gain score 0.25. Based on test result difference in average value of cognitive learning between experimental and control group showed the tcount of the pretest was 1.89 and the tcount of the posttest was 4.49 is higher than the ttable it was 1.67. Based on the result of the research, it can be concluded that the science comics for sound and auditory system material based on Problem Based Learning is effective to create the students learning motivation and improve the learning outcomes.